Probing into the diversity of trypanosomatid flagellates parasitizing insect hosts in South-West China reveals both endemism and global dispersal - Votýpka, Jan; Maslov, Dmitri A; Yurchenko, Vyacheslav; Jirků, Milan; Kment, Petr; Lun, Zhao-Rong; Lukes, Julius (Molecular phylogenetics and evolution, 2010)
Flagellates of the class Kinetoplastea are known to frequently parasitize insects. We have collected 67 isolates from 407 Heteroptera hosts captured in several locations of South-West China. Their splice leader (SL) RNA gene repeats and small subunit (SSU) rRNA genes were PCR amplified from the infected tissue samples. In most cases, parasites were found in the midgut, rarely the infection was confined to the Malpighian tubes. Phylogenetic analysis of the obtained sequences has significantly expanded the known diversity of these monoxenous parasites. Fifteen typing units were found among these isolates including 11 potentially new species. Four typing units matched the previously known typing units from the Neotropics indicating a global distribution of the respective parasite species. At the same time, new clades appeared, testifying for a certain level of endemism. The host record of the parasites found indicated a variable specificity level of the host-parasite association including several cases of a very broad host range. Our results disprove the "one host - one parasite" paradigm and show that although the global diversity of monoxenous parasites is high, it is not as enormous as suggested earlier. Moreover, phylogenetic analysis revealed the presence, among the isolated strains, of a new Phytomonas species, which is the first documentation of this potentially pathogenic dixenous parasite of plants in China.
Keywords: protozoální DNA; China; Genes, Protozoan; Insecta; druhová specificita; zeměpis; Host-Parasite Interactions; fylogeneze; interakce hostitele a parazita; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; molekulární evoluce; Evolution, Molecular; sekvenční seřazení; Geography; DNA, Protozoan; Species Specificity; geny rRNA; protozoální geny; Trypanosomatina; Animals; Genes, rRNA; hmyz; zvířata; Čína; Sequence Alignment